Ruwah Eid Tradition (Study of Local Wisdom as a Strategy for Unifying Multicultural Societies in West Bangka) - Tiara Ramadhani; Aruna Asista (Institut Agama Islam Negeri Ponorogo, 2025)
One of the traditions in Bangka Belitung that is still carried out and preserved is the ruwahan tradition, which is celebrated once a year, approaching the month of Ramadan. This study is interesting to do considering that there have been many shifts in traditions and cultures in society in the modern era. However, the ruwahan tradition is still carried out and preserved by the community by upholding local wisdom. This ruwahan tradition is carried out by older people, but teenagers and children also enliven this tradition. Another uniqueness of this ruwahan tradition is that it can bring people from various regions together to socialize and enliven it. The excitement of the ruwahan tradition exceeds the traditions of Eid al-Fitr and Eid al-Adha. This study chose the locus in West Bangka Regency because the tradition is still preserved and carried out. Many people flock to West Bangka to enliven the ruwahan tradition. The data collection techniques that researchers will use are interviews, observations, and documentation, with the research subjects being the local community, community leaders, traditional leaders, and people outside the local community of West Bangka Regency.